Impact of Health Literacy via Leaflets on Preventing Multimorbidity Non-Communicable Diseases in Tanggobu Village - Rahmawati; Sunarsih; Fitri Yanti; Komang Ayi Sukma (Media Publikasi Promosi Kesehatan Indonesia (MPPKI), 2024)
Background: Health literacy is closely related to multimorbidity. Health Literacy is defined as the extent to which an individual has the capacity to obtain, process and understand basic health information and the need for services to make appropriate health decisions. Tanggobu Village is an area which is a mining area which is a village in Morosi District, Konawe Regency. Based on the results of previous research, it was found that 90.9% of elderly people suffer from multimorbid diseases in the Tanggobu Village community, that the majority of people suffer from hypertension. Efforts to prevent multimorbidity from non-communicable diseases can be done by increasing health literacy, which is a concept consisting of four competencies, namely the process of accessing, understanding, assessing and applying information. Objective: To determine the effect of health literacy on preventing multimorbidity from non-communicable diseases in the Tanggobu village community, Morosi District, Konawe Regency. Method: This type of research is quantitative, Experimental research with one group pretest-posttest design. The population and sample were 30 respondents with sampling using total sampling. Statistical analysis uses a paired t-test (paired sample t-test). Results: The results of the paired sample t-test show (p-value = 0.000), where the p-value < ? value. Conclusion: There is influence of health literacy through leaflet media about preventing multimorbidity of non-communicable diseases on the knowledge of the Tanggobu village community, Morosi District. Konawe Regency. recommendations from research results are distributing leaflets more widely, including in health centers, schools, workplaces and local communities to reach more people, Apart from leaflets, integrate health literacy through various media such as educational videos, social media and health applications to reach people with various media preferences.